2019
DOI: 10.3390/foods8120692
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Next-Generation Disinfectant: Composition, Storability and Preservation Potential of Plasma Activated Water on Baby Spinach Leaves

Abstract: Plasma activated water (PAW) has rapidly emerged as a promising alternative to traditional sanitizers applied in the fresh produce industry. In the present study, PAW chemistry and storage stability were assessed as a function of plasma operating conditions. Increasing plasma exposure time (5, 12.5, 20 min) and power (16, 26, 36 W) led to a significant drop in pH (2.4) and higher nitrates and nitrites levels (320 and 7.2 mg/L, respectively) in the PAW. Non-detectable hydrogen peroxide concentration, irrespecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…In a similar study, the effect of PAW (11 kV for 20 min) on the color (L, a, and b values) of spinach leaves after storage at 4 °C for eight days was compared with the changes in the untreated samples [ 59 ]. The control (untreated) and PAW treated samples showed no significant difference in color evaluated using L, a, and b values, which indicated the “fresh-like appearance”.…”
Section: The Effect Of Paw On Sensory Attributes and Consumer Accementioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study, the effect of PAW (11 kV for 20 min) on the color (L, a, and b values) of spinach leaves after storage at 4 °C for eight days was compared with the changes in the untreated samples [ 59 ]. The control (untreated) and PAW treated samples showed no significant difference in color evaluated using L, a, and b values, which indicated the “fresh-like appearance”.…”
Section: The Effect Of Paw On Sensory Attributes and Consumer Accementioning
confidence: 99%
“…The control (untreated) and PAW treated samples showed no significant difference in color evaluated using L, a, and b values, which indicated the “fresh-like appearance”. It was shown that multiple rinsing with water affected the color as there was an increase in the yellowness (b values), which was not seen with the PAW treated samples [ 59 ]. In another study by Ma et al [ 55 ] using PAW treatment (10 kHz sinusoidal high-voltage source at 18 kV), the change in color and firmness of the treated and untreated strawberries were compared after storage at 20 ± 2 °C and 70 ± 5% RH for four days [ 55 ].…”
Section: The Effect Of Paw On Sensory Attributes and Consumer Accementioning
confidence: 99%
“…It has been widely reported that such an environment is suitable for silver reduction [ 21 ]. A recent application of CP technology is the production of plasma activated water (PAW) through the exposure of water to a CP discharge, e.g., using air as the working gas (creating air plasma), leading to the formation of a combination of reactive oxygen and nitrogen species (RONS) [ 22 ]. PAW is classified neither as a chemical reagent nor a natural resource, but as purified water, which contains a cocktail of reactive oxygen and nitrogen species [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, plasma has shown a promising effect in plant growth promotion, pest control, toxin removal, agrochemical dissipation, cancer therapy, tissue regeneration, etc. [3]. However, a few researchers revealed that applying the gas plasma directly over the food surface can cause loss of color and degradation of bioactive compounds [4].…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of MC results from the presence of RONS, which causes damage to the cell membrane, cell wall and DNA, cell shrinkage and cytoplasmic leakage. Some of the studies have focused on the use of MC as a plant disinfectant [3], food disinfectant [9][10][11], and inducer for plant growth [12].…”
Section: Introductionmentioning
confidence: 99%